Broun, William. William Broun to Harriet C. Johnson Broun, Charlottesville, VA, December 23, 1860. - Broun, William (Valdosta State University Archives and Special Collections, 2020., 1860)
University of Virginia December 23rd 1860 Dear Ma, You highly praised and much appreciated letter of the 5th
Handwritten letter from William Broun to his mother, Harriet C. Johnson Broun. December 23, 1860. University of Virginia. Charlottesville, Virginia, United States. 4 pages on two sheets of paper.
Keywords: Broun, William, Captain, 1842-1908; American Civil War (1861-1865); Broun, Harriet C. Johnson, 1824-1908; Christmas; College Students; Personal correspondence; Slavery; University of Virginia; Virginia--Bloomfield; Virginia--Northumberland County; Virginia; Virginia--Charlottesville